Food blog review experience of Filipino consumers - Santos-Ocampo, Maria Regina Angeles Sunico
The purposes of the study were to analyze the content and structure of a food blog review, to describe the demographic characteristics of food blog readers and their behavior and attitude toward food blog reviews. Using survey research, a survey questionnaire was posted on a free web based site and in various social networking sites for which volunteer respondents answered the survey through e-mail. The sample size of 86 respondents consisted of male and female Filipinos between the ages of 21 to 35 were collected through snowball sampling. A checklist was used to analyze and describe ten active online food blog reviews to enable the researcher to describe how a food blogger creates an online food review. Results show that 69 out of the 86 respondents primarily use online food blogs as a main source of finding out information about higher price point food products and food establishments. Findings revealed that the respondents think that food blogs can be a reliable source of information provided that the food blog review includes an objective and detailed descriptions of the food, description regarding service and food quality, and photographs that represent the details being described in the food blog post. The study suggests that food blogs affect the decisions and purchasing behaviors of consumers. Food blog authors provide consumers with easily accessible information about their personal experience with a particular establishment of product that aids in their decision to purchase. It was gathered that 64 out of 68 respondents stated to have purchased food items after reading a food blog review. The study recommends future similar studies that may include the extent of reliability of the posted food blog review after a consumer's decision to purchase from a featured food establishment. Moreover, the study encourages researches that include comparisons of unsponsored food blogs versus food blogs that are deliberately for advertising purposes only.